Heterogeneous effects of a minimum wage increase on hours worked - Paul Redmond; Séamus McGuinness (The Economic and Social Research Institute (ESRI), 2021)
This study uses new administrative earnings data, linked to the Irish Labour Force Survey, to analyse the impact of three successive minimum wage increases that took place over the period 2016 to 2018, on the hours worked of minimum wage employees. The study allows for the assessment of the cumulative impact of minimum wage increases that might otherwise be missed in frameworks that examine the yearly policy effect at a particular point in time. This is important as the yearly rate rises from 2016 to 2018 may have a small effect in any one particular year, while amounting to a significant cumulative effect when added together. The data at hand are also sufficient to allow us to test for heterogeneous impacts across different types of minimum wage workers depending on contract type, sector and region.
Keywords: 330; Mindestlohn; Wirkungsanalyse; Arbeitszeit; Irland